MODERN CONCEPT OF OFFICIALITY (PUBLICITY) OF CRIMINAL PROCEEDINGS AND DEVELOPMENT TENDENCIES - Baghdasaryan, Gevorg (State and Law, 2025)
The article is dedicated to the principle of officiality of criminal procedure. It presents the modern concept of officiality, discusses the expression of this idea in the Criminal Procedure Code of the Republic of Armenia, and highlights the tendencies of its development in the context of practical realities.As a result of the conducted research, the Author states that the modern concept of officiality in criminal procedure is the relative unity of public and private interests. It implies that the criminal proceedings are conducted with the purpose of uncovering the offence and imposing legal consequences for it, and during this process, human rights and freedoms must be guaranteed proportionately. The principle of officiality requires that, on the one hand, the norms governing the procedure of investigation and the powers of criminal prosecution bodies do not unnecessarily endanger human rights, while on the other hand, the guarantees of human rights and freedoms do not excessively limit the procedural possibilities for investigating and uncovering offences.According to the Author, the concept of officiality in the criminal justice system of the Republic of Armenia is expressed in line with its new concept and reflects the influence of universal tendencies in the correlation of public and private interests. The Author argues that the criminal procedure legislation of the Republic of Armenia, while strengthening the officiality of criminal proceedings in determining the status of a court, at the same time, for the purpose of alleviating the burden on criminal procedure, has increased the degree of dispositivity by expanding the opportunities of private participants in the proceedings to pre-determine the outcomes of public matters. Criminal procedural legislation and practice clearly bear the tendencies of general development in the relationship between public and private interests, strengthening private interests at the expense of limiting the possibilities for public action.
Keywords: officiality; dispositivity; ex officio examination; reasonableness; principle; basis; public interest; private interest